Synthesis and Antimicrobial Activity of Dithiocarbamates of ω-Substituted (2-naphthyloxy)alkanes - Zaidi, Sadaf; Chaturvedi, Devdutt; Saxena, Mridula; Srivastava, Richa (Asian Journal of Chemistry, 2019)
A series of dithiocarbamates of ω-substituted (2-naphthyloxy) alkanes was developed through condensation of 2-(2-chloro-alkoxy)-naphthalene to various kinds of aliphatic, aromatic, alicyclic, heterocyclic primary and secondary amines employing benzyl trimethyl ammonium hydroxide in catalytic quantity (Triton-B/CS2 system) afforded desired products in high yields (82-98 %). The complete series of synthesized compounds (4-48) were evaluated for antimicrobial activity through microdilution method using various bacterial and fungal strains. The antifungal and antibacterial values were estimated as MIC values. Fluconazole and ciprofloxacin [16 to 0.03 μg/mL] were used as the standard antifungal and antibacterial drug, respectively. Out of series of evaluated compounds, some of these compounds such as compounds 28, 29, 30, 31, 32, 33 have displayed maximum potency which is comparable to standard drugs.